Compartment-specific aggregases direct distinct nuclear and cytoplasmic aggregate deposition - Miller, Stephanie Barbara Maria; Ho, Chi-Ting; Winkler, Juliane; Khokhrina, Maria; Neuner, Annett; Richter, Karsten; Schiebel, Elmar; Mogk, Axel; Bukau, Bernd (The EMBO journal, 2015)
Abstract Disruption of the functional protein balance in living cells activates protective quality control systems to repair damaged proteins or sequester potentially cytotoxic misfolded proteins into aggregates. The established model based on Saccharomyces cerevisiae indicates that aggregating proteins in the cytosol of eukaryotic cells partition between cytosolic juxtanuclear (JUNQ) and peripheral deposits. Substrate ubiquitination acts as the sorting principle determining JUNQ deposition and subsequent degradation. Here, we show that JUNQ unexpectedly resides inside the nucleus, defining a new intranuclear quality control compartment, INQ, for the deposition of both nuclear and cytosolic misfolded proteins, irrespective of ubiquitination. Deposition of misfolded cytosolic proteins at INQ involves chaperone-assisted nuclear import via nuclear pores. The compartment-specific aggregases, Btn2 (nuclear) and Hsp42 (cytosolic), direct protein deposition to nuclear INQ and cytosolic (CytoQ) sites, respectively. Intriguingly, Btn2 is transiently induced by both protein folding stress and DNA replication stress, with DNA surveillance proteins accumulating at INQ. Our data therefore reveal a bipartite, inter-compartmental protein quality control system linked to DNA surveillance via INQ and Btn2.
Gesehen am 08.06.2020